1991
DOI: 10.1002/pssa.2211240206
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram and Optical Energy Gaps for CuInyGa1−ySe2 Alloys

Abstract: The T(y) phase diagram of the alloys CuInyGa1−ySe2, prepared by the chemical vapor deposition method, is obtained from X‐ray diffraction and differential thermal analyses. It is found that in addition to the chalcopyrite structure, a zincblende In2Se3‐rich phase and a zincblende Ga2Se3‐rich plus liquid two‐phase field, are obtained. Also it is found that the variation of the lattice parameter ratio c/a is not linear with composition but varies from 1.96 to 2.00 as y is increased from 0.0 to 0.6 and c/a being e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 10 publications
7
43
0
1
Order By: Relevance
“…17) De Micco et al reported that the mass loss started at 773 K in the chlorination reaction of metallic copper at the volatilization rate of 10 ¹3 mg s ¹1 , and increases at 1023 K to one order of magnitude larger than that at 773 K. 18) In summary, extraction of the elements from Cu(In,Ga)Se 2 by vaporization is basically possible. It is considered that the solidvapor reaction takes place in the present experimental conditions, as the liquidus temperature of CuIn 0.7 Ga 0.3 Se 2 is ³1323 K. 19) Above the liquidus temperature, it is expected that the chlorination reaction occurs via vaporliquid reaction in which the activity of both products and reactants has significant influence on the reactivity and the evaporation behavior.…”
Section: Effect Of Temperaturementioning
confidence: 92%
“…17) De Micco et al reported that the mass loss started at 773 K in the chlorination reaction of metallic copper at the volatilization rate of 10 ¹3 mg s ¹1 , and increases at 1023 K to one order of magnitude larger than that at 773 K. 18) In summary, extraction of the elements from Cu(In,Ga)Se 2 by vaporization is basically possible. It is considered that the solidvapor reaction takes place in the present experimental conditions, as the liquidus temperature of CuIn 0.7 Ga 0.3 Se 2 is ³1323 K. 19) Above the liquidus temperature, it is expected that the chlorination reaction occurs via vaporliquid reaction in which the activity of both products and reactants has significant influence on the reactivity and the evaporation behavior.…”
Section: Effect Of Temperaturementioning
confidence: 92%
“…1 shows preferential texturing of the 112 refl ection relative to the others. In particular, the intensity ratio I (112) /I (220/204) was ~5 and exceeded by several times the intensity ratio of these refl ections that was characteristic for randomly oriented CIGS powders [11,12]. This confi rmed that the grains of the studied CIGS thin fi lms were textured in the 〈112〉 direction.…”
mentioning
confidence: 53%
“…The calculation was performed by averaging all possible angular positions of line pairs in the x-ray pattern with indices (112)-(220/204), (112)-(312/116), (112)-(316/332), (220/204)-(312/316), and (220/204)-(316/332). A comparison of the unit-cell constants found by us using both methods and x-ray structure data for CuIn 1-x Ga x Se 2 solid solutions with various Ga concentrations in the range 0 < x < 1 [11][12][13] allowed the composition of the studied fi lms to be estimated as x ~ 0.45. Table 1 presents the elemental composition of CIGS fi lm that was determined by EDX and SAES.…”
mentioning
confidence: 99%
“…However, these temperatures also exceed the vaporization temperature of Se, T vap : Se ¼ 685°C, 72 leading to Se loss, and are potentially above the melting temperature of CISe (990°C). 73 Sub-stoichiometric amounts of Se lead to absorber layers with poor opto-electronic performance and which have melted, as discussed above. 73 Melted CISe dewets from the Mo substrate forming micrometer droplets.…”
Section: Annealing Of Cu/in/se Stacksmentioning
confidence: 99%
“…73 Sub-stoichiometric amounts of Se lead to absorber layers with poor opto-electronic performance and which have melted, as discussed above. 73 Melted CISe dewets from the Mo substrate forming micrometer droplets. 70 In an effort to further reduce LA time, Walter et al 74 increased the reactivity of their SEL precursors by depositing the precursor as nine layers (i.e., three stacks of Cu/(In or Ga)/Se).…”
Section: Annealing Of Cu/in/se Stacksmentioning
confidence: 99%